1987
DOI: 10.1115/1.3248083
|View full text |Cite
|
Sign up to set email alerts
|

Forced Convection Cooling Across Rectangular Blocks

Abstract: Conjugate heat transfer for two-dimensional, developing flow over an array of rectangular blocks, representing finite heat sources on parallel plates, is considered. Incompressible flow over multiple blocks is modeled using the fully elliptic form of the Navier-Stokes equations. A control-volume-based finite difference procedure with appropriate averaging for the diffusion coefficients is used to solve the coupling between the solid and fluid regions. The heat transfer characteristics resulting from recirculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
2

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(56 citation statements)
references
References 5 publications
6
48
2
Order By: Relevance
“…The conjugate solution of uniformly heat generating components on air-cooled electronic boards, in two-dimensional flow configurations, is reported in [11][12][13] using the Simpler algorithm [14]. All of these flows were assumed to be time independent, which limits their applicability to only steady flows.…”
Section: Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…The conjugate solution of uniformly heat generating components on air-cooled electronic boards, in two-dimensional flow configurations, is reported in [11][12][13] using the Simpler algorithm [14]. All of these flows were assumed to be time independent, which limits their applicability to only steady flows.…”
Section: Motivationmentioning
confidence: 99%
“…Therefore, an exponential-like curve represents the convective performance for each board. In the upstream region, special correlations account for entrance effects [12], whereas in the fully-developed region, the value of the heat transfer coefficient remains approximately uniform. However, if the components are not geometrically similar, as often is the case, different correlations are used for each component.…”
Section: Stage Threementioning
confidence: 99%
See 1 more Smart Citation
“…They found that increasing the spacing between the blocks produces a better cooling of blocks. Davalath and Bayazitoglu (1987) studied the laminar forced convection over an array of heat generating rectangular blocks. They showed that the vertical faces of the heat generating blocks are not efficiently cooled.…”
Section: Introductionmentioning
confidence: 99%
“…Open cavity flow is also found in electronic block arrays. In this context, Davalath and Bayazitoglu [19] made a work by considering the each block under constant heat flux boundary conditions. Then, some of the studies are focused on to enhance heat transfer in blocked channels.…”
Section: Introductionmentioning
confidence: 99%